Forest Owners' Intentions to Implement Environmentally Oriented Forest Management Practices: A Case from Eastern Finland - Häyrinen, Liina; Kaseva, Janne; Pouta, Eija (Springer Nature, 2025)
Forests and forest management are crucial in achieving environmental objectives, including mitigating climate change by sequestering carbon, preserving biodiversity, and preventing the eutrophication of surface waters. Achieving environmental objectives heavily depends on the willingness of private forest owners to adopt environmentally oriented forest management practices (EFMPs). This study investigates private forest owners' intentions to implement specific EFMPs, including increasing the proportion of deciduous trees, ash fertilization on peatlands, extending rotation periods, implementing continuous cover forestry, and adding deadwood and retention trees. Guided by the theory of planned behavior, we explore how Finnish forest owners' beliefs about EFMPs, attitudes towards environmental objectives, subjective norms (SN), and perceived behavioral control (PBC) influence their intentions to implement EFMPs. A postal survey was conducted among forest owners in the Lake Puruvesi region of eastern Finland (n = 102). The data were analyzed using structural equation models (SEM). The findings indicate that forest owners generally have evident intentions to implement EFMPs. ATT towards environmental objectives had the strongest positive impact, while SN and PBC had no significant influence on the intention to implement EFMPs. The findings suggest that in promoting EFMPs, policy efforts should focus on evidence-based information regarding water protection and biodiversity impacts. Forest owners’ attitudes and subjective norms concerning carbon sequestration are less prominent compared to their views on water protection and biodiversity.
Keywords: sustainable forest management; forestry practices; forest owners; perceptions; decision-making